Study of gut microbiota in cholangiocarcinoma patients - O. S. Fedorova; A. Е. Kovshirina; T. S. Sokolova; V. V. Kulenich; L. M. Ogorodova (Бюллетень сибирской медицины, 2025)
Aim. To analyze the taxonomic composition of the intestinal microbiota in patients with cholangiocarcinoma (CCA) and compare it to individuals without oncopathology. Materials and methods. The study included patients with histologically verified cholangiocarcinoma (n = 30) and a control group (n = 27). An integrated approach was used, including clinical and anamnestic, laboratory, and instrumental methods. The intestinal microbiota was studied through amplicon sequencing of the bacterial 16S rRNA gene. Results. The assessment of alpha- and beta-diversity of the microbiota in patients with CCA did not show any significant differences compared to the control group. However, a comparative analysis revealed changes in the representation of a number of microorganisms at different taxonomic levels, including a higher content of Bacteroides and Lachnospiraceae_NK4A136_group in patients with CCA. Additionally, bacteria that influence the change in the global balance of microorganisms were identified in both groups, such as [Ruminococcus]_torques_group, Subdoligranulum, Parasutterella, unclassified Firmicutes in samples of patients with CCA and Oscillospiraceae and Erysipelotrichaceae UCG-006 in the control group. Conclusion. The study found a number of significant differences in bacterial representation between patients with cholangiocarcinoma and control group participants. Further research on the intestinal microbiota has the potential to develop non-invasive tools for early diagnosis of CCA.